Pemanfaatan Teknologi Informasi dan Pengawasan Keuangan terhadap Kualitas Laporan Keuangan - Lusiana Kanji; Yudi Akhmad Sadeli (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
The purpose of this study was to determine the Utilization of Information Technology and Financial Oversight on the Quality of Financial Reports in Anrihua Village, Kindang District, Bulukumba Regency. The research method used in this study is a quantitative research method using a descriptive approach. The population in this study were all apparatus of Anrihua Village, Kindang District, Bulukumba Regency, totaling 38 people.This study used a saturated sample, which took the entire population. The sample size in this study was 38 samples which included all apparatus of Anrihua Village, Kindang District, Bulukumba Regency. The results showed that the use of information technology had no positive and insignificant effect on the quality of financial reports in Anrihua Village, Kindang District, Bulukumba Regency. Meanwhile, financial supervision has a positive and significant effect on the quality of financial reports in Anrihua Village, Kindang District, Bulukumba Regency